El sector financiero y su compromiso con la comunidad - María José Tejera (Atlantic Review of Economics, 2016)
– The maximization of profit as the main objective of companies is being criticized from different forums, advocating for an economic system in which the achievement of social sustainability will play a leading role. In the banking sector, after the outbreak of the crisis in 2008, financial bailouts that have used public funds to save various entities have provoked a current of opinion about the necessary social role that banking companies must develop. In this article, a case study is carried out analyzing the role of Corporate Social Responsibility (CSR) in ABANCA, the financial institution with the largest presence in Galicia (northwest Spain), which has been rescued with public money, Identifying a series of objectives and actions carried out by said entity. The analyzes carried out show, among others, the importance of trust and transparency, as well as attention to intangibles.
Keywords: G30; G38; L21; M14; 330